Evaluasi Pedidikan di Madrasah Ibtidaiyah Nurul Muttaqin Kuala Mandor B Kubu Raya - Ahmad Fahtul rizal; Samiyah (putrapublisher.org, 2023)
The purpose of this study is to describe the evaluation of learning carried out at Madrasah Ibtidaiyah Nurul Muttaqin Kuala Mandor B. The method used is descriptive qualitative. Data collection techniques are carried out by observation (observation), interviews, and documentation. Data analysis was carried out through three stages, namely data reduction, data presentation, and drawing conclusions. The results and discussion show that the evaluation conducted at Madrasah Ibtidaiyah Nurul Muattaqin Kuala Mandor included formative evaluation and summative evaluation. The formative evaluation carried out included several things, including assignments, written tests, practical tests, group discussions, observation, portfolios, and reflection. The summative evaluation is carried out using tests or exams based on the basic competencies that students must master. The aim is to find out the progress of student learning and provide input for teachers as a reference for improving learning in the future. Assessments in this summative evaluation include Final Semester Assessments (PAS), Final Year Assessments (PAT), Madrasah Examinations (UM), and others related to testing students after completing the learning process in a certain period of time. With formative and summative evaluations that have been carried out at Madrasah Ibtidaiyah Negeri 1 Sukabumi, it can be useful for improving student learning outcomes in the future.